Lactic Acid Bacteria Isolated from Japanese Fermented Fish (Funa-Sushi) Inhibit Mesangial Proliferative Glomerulonephritis by Alcohol Intake with Stress - Shima, Jun; Morikawa, Shunichi; Endou, Masumi; Yamada, Yumiko; Komatsuzaki, Noriko (Journal of nutrition and metabolism, 2018)
The aim of this study was to examine the effect of heat-killed Lactobacillus paracasei NFRI 7415 on kidney and bone in mice fed an ethanol-containing diet with stress. Eight-week-old Cril : CD1 mice were fed a control diet (CD), an alcohol diet (AD) (35.8% of total energy from ethanol), or an alcohol diet containing 20% heat-killed Lb. paracasei NFRI 7415 (107 CFU/g) (LD) for 4 weeks. Mice in the AD and LD groups also underwent restraint stress for two weeks from 13 days. The mice were placed in a 50 mL plastic tube, which had a small hole drilled around its base to allow ventilation, and restrained for 1 h every day. High final body weight was in the following order: CD, LD, and AD (p<0.05). The heat-killed Lb. paracasei NFRI 7415 lowered liver total cholesterol concentration and plasma glutamic-oxaloacetic transaminase (GOT) level. In addition, fecal bile acids of the LD group were higher than in the AD group (p<0.05). The glomerulus of the kidney in the AD group was observed to be more fibrotic than in the CD and LD groups with azan stain. Immunostaining confirmed that brown areas indicating the existence of mesangial cells were increased in the AD group, but not in the CD and LD groups. These results indicated that the heat-killed Lb. paracasei NFRI 7415 inhibited mesangial proliferative glomerulonephritis by alcohol intake with stress.